2018
DOI: 10.1080/09168451.2018.1491285
|View full text |Cite
|
Sign up to set email alerts
|

Purification, cDNA cloning, and characterization of plant chitinase with a novel domain combination from lycophyte Selaginella doederleinii

Abstract: AtChiC: Arabidopsis thaliana class V chitinase; CBB: Coomassie brilliant blue R250; CBM: carbohydrate binding module family; CrChi-A: Cycas revolute chitinase-A; EaChiA: Equisetum arvense chitinase-A; GH: glycoside hydrolase family, GlxChi-B: gazyumaru latex chitinase-B; GlcNAc: N-acetylglucosamine; HPLC: high performance liquid chromatography; LysM; lysin motif; MtNFH1: Medicago truncatula ecotypes R108-1 chitinase; NCBI: national center for biotechnology information; NF: nodulation factor; NtChiV: Nicotiana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Under the same conditions, the chitin-binding ability of PrChiA is lower than chitinase from Equisetum arvense (EaChiA), but the binding mode of these two chitinases for (GlcNAc) n are comparable [80,81]. The cleavage patterns of (GlcNAc) n produced by chitinase from Selaginella doederleinii (SdChiA) are also similar, except for (GlcNAc) 4 which is mainly hydrolyzed to (GlcNAc) 2 [82].…”
Section: Plantsmentioning
confidence: 97%
See 1 more Smart Citation
“…Under the same conditions, the chitin-binding ability of PrChiA is lower than chitinase from Equisetum arvense (EaChiA), but the binding mode of these two chitinases for (GlcNAc) n are comparable [80,81]. The cleavage patterns of (GlcNAc) n produced by chitinase from Selaginella doederleinii (SdChiA) are also similar, except for (GlcNAc) 4 which is mainly hydrolyzed to (GlcNAc) 2 [82].…”
Section: Plantsmentioning
confidence: 97%
“…The mode of interaction of LysM in the chitinases among plants may differ, for example, LysM acting in chitin-signaling immunity in fern and higher plants, which have been extensively studied. For subtropical plant species, i.e., fern and moss, the recent research reported LysM-containing chitinases from Pteris ryukyuensis [78,79], Equisetum arvense [80,81], Selaginella doederleinii [82], and moss Bryum coronatum [83]. The LysM domains of chitinase PrChiA from Pteris ryukyuensis are demonstrated to bind to chitin and COS. (GlcNAc) 6, (GlcNAc) 5 , and (GlcNAc) 4 are the most frequently hydrolyzed into (GlcNAc) 4 +(GlcNAc) 2, (GlcNAc) 3 +(GlcNAc) 2 , and (GlcNAc) 3 +GlcNAc, respectively.…”
Section: Plantsmentioning
confidence: 99%